Coal bottom ash lightweight brick - Nur Farhayu, Ariffin; Khairunisa, Muthusamy; Fadzil, Mat Yahaya; Sharifah Maszura, Syed Mohsin; Khairul Anuar, Shahid; Saffuan, Wan Ahmad; Abdul Muiz, Hasim; Muhammad Nor Syahrul, Zaimi; Nurul Natasha, Nasrudin; Muhammad Rafie, Ashaari; Nor Hasanah, Abdul Shukor Lim; Mohd Warid, Hussin; et al. (2021)
100% and 50% replacement with coal ash. Reduce 40% of production cost. 20% less dense compare conventional brick.